2016
DOI: 10.1016/j.scitotenv.2015.10.089
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus co-limitation and grazing moderate nitrogen impacts on plant growth and nutrient cycling in sand dune grassland

Abstract: Atmospheric nitrogen (N) deposition alters plant biodiversity and ecosystem function in grasslands worldwide. This study examines the impact of 6 years of nutrient addition and grazing management on a sand dune grassland. Results indicate that co-limitation of N and phosphorus (P) moderates the impact of realistic rates of N addition (7.5, 15 kg N ha −1 year −1 ). Combined NP addition (15 kg N + 10 kg P ha −1 year −1 ) was the only nutrient treatment to differ significantly from the control, with greater above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…In a field study in the Netherlands, vegetation did not respond to N-fertilization at all (Ten Harkel and van der Meulen, 1995). In a field study in Wales, biomass first increased with Nfertilization (Plassmann et al, 2009), but after six years, only with N and P combined (Ford et al, 2016).…”
Section: Nutrient Availability In Different Dune Zonesmentioning
confidence: 97%
See 1 more Smart Citation
“…In a field study in the Netherlands, vegetation did not respond to N-fertilization at all (Ten Harkel and van der Meulen, 1995). In a field study in Wales, biomass first increased with Nfertilization (Plassmann et al, 2009), but after six years, only with N and P combined (Ford et al, 2016).…”
Section: Nutrient Availability In Different Dune Zonesmentioning
confidence: 97%
“…Also, the response of Grey dunes to high N-deposition partly depends on the chemical status of the soil and availability of P (Kooijman et al 1998;Kooijman and Besse, 2002;Kooijman et al, 2009). The effect of grazing, applied to counteract grass encroachment (Ford et al, 2016), may be determined by soil chemistry as well. Furthermore, cumulative N-deposition, i.e., the total N-deposition cumulated over time, may have led to increased N-levels in the soil, as in forest ecosystems (Mulder et al, 2015), or increased net N-mineralization, as in inland dunes (Sparrius and Kooijman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the perennial patches provide favorable soils with lower EC and pH but higher SOM for dominant species and forbs, such as L. chinensis, Medicago ruthenica, Thalictrum simplex and Kalimeris integrifolia, which are species demanding relatively rich nutrient and low alkaline-salinity stress levels. Here the higher richness could be interpreted mainly as an effect of abundant organic matter, the limiting factors for plant biomass accumulation (Roem and Berendse 2000;Ford et al 2016). Specifically, the clonal perennial grasses, L. chinensis and P. australis, can respond to habitat heterogeneity by shifting their morphology and architecture (Wang et al 2017).…”
Section: Spatial Pattern Of Plant Variables and Soil Propertiesmentioning
confidence: 99%
“…Various factors control the dynamic changes in the content of P fractions, including soil texture (TokuraI et al, 2011), management systems , chemical and organic fertilizers (Liu et al, 2020;Gichangi et al, 2009), and biology (Beutler et al, 2015;Li, 2001). Previous studies have shown that overgrazing may hinder the mineralization of phosphorus (Ford et al, 2016) and reduce its solubility (Sigua et al, 2014). Moreover, Li (2001) reported that long-term grazing reduced the soil P stock-particularly for organic P (Po).…”
Section: Introductionmentioning
confidence: 99%